Legal Review of Birth Certificate Cancellation Due to Data Verification Errors in the Population Administration System (Analysis of Decision Number 19/G/2020/PTUN/YK) - Wahyu Nurristiana; Nanik Sutarni; Adhiputro Pangarso Wicaksono (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
This study aims to examine the juridical aspects of the annulment of a birth certificate issued due to verification errors in the digital-based population administration system, focusing on the Decision of the Administrative Court (PTUN) of Yogyakarta Number 19/G/2020/PTUN/YK. In this case, the birth certificate under the name of Setyowati was issued by the Civil Registration and Population Service (Dukcapil) of Bantul Regency by listing her grandmother as her biological mother. This error not only raised administrative issues but also potentially affected the civil inheritance rights of legitimate heirs. This research employs a normative juridical method with a descriptive-analytical approach, supported by a literature review, analysis of statutory regulations, the principles of good governance (AUPB), the doctrine of material truth, and an in-depth review of the court’s decision. The findings reveal that the Defendant (Dukcapil), who only conducted administrative verification through the Population Administration Information System (SIAK) without factual examination, violated the principles of accuracy, legal certainty, and justice. The panel of judges emphasized that a birth certificate as a state legal product must reflect material truth, not merely the formal completeness of documents. This decision not only annulled a legally flawed birth certificate but also highlighted the urgency of reforming verification systems in digital-based population administration services. The existing system must be supported by competent and ethical human resources, field verification mechanisms, and effective internal supervision to prevent data manipulation that may harm other parties. This study is expected to provide an academic contribution to the development of administrative law, as well as a practical reference for public service institutions to strengthen accuracy, accountability, and fairness in issuing population documents.